PRODUKSI NIRA AREN DI AREAL GARAPAN KELOMPOK TANI HUTAN HARAPAN BARU I DALAM TAMAN HUTAN RAYA WAN ABDUL RACHMAN - Inka Kumala Dewi; Indriyanto .; Ceng Asmarahman (Fakultas Kehutanan Universitas Winaya Mukti, 2022)
The Harapan Baru I Forest Farmers Group is one of the forest farmer groups in the Wan Abdul Rachman Great Forest Park. In the cultivated land of the Harapan I Forest Farmers Group, there are productive sugar palm trees as a producer of palm sap. Sugar palm is a tree belonging to the Palmae family. The objectives of this research were to determine of sugar palm sap production at the cultivated land of the Harapan Baru I Forest Farmer Group. The research was carried out in November until December 2021. The method used was the direct observation in the field related to the volume of sugar palm sap. In addition, a simple regression analysis was carried out to determine effect the height of the growing place on the production of sugar palm sap. The results obtained, there are 9 individuals are being harvested sap. The average production of sugar palm sap is 16.7 l/tree per day. The production of sugar palm sap is influenced by the height of the place where it grows and the age of the sugar palm tree. The higher the place to grow, the more sugar palm sap produced. The largest production of sugar palm sap is obtained from sugar palm trees 10—15 years old, which is 29.8 l/tree. The production of sugar palm sap at the cultivated land of the Harapan Baru I Forest Farmers Group I in the Wan Abdul Rachman Great Forest Park is in the medium category.